Shift from Cultural Property to Cultural Heritage and its Possible Consequences for International Criminal Law - Ryška, Ivan (Polish Review of International and European Law, 2021)
The article examines the content of terms ‘cultural property’ and ’cultural heritage’. It illustrates the continual development in the protection of cultural property that evolved into the concept of cultural heritage. The first part of the article describes differences between the two notions and explains why the term ’cultural heritage’ is more suitable for the current approach to protection of cultural expressions. The second part of the article deals with possible consequences that the conceptual shift from cultural property to cultural heritage can bring to protection under International Criminal Law. It argues that despite the wording of relevant legal documents, it does not explicitly work with the term ’cultural heritage’. The author notes that jurisprudence of international criminal tribunals has already been recognizing this concept and reflecting upon the extent of the term in some of their decisions.